2015
DOI: 10.2340/00015555-1895
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use in Patients with Psoriasis After the Introduction of Biologics in Sweden

Abstract: The introduction of biologics has changed treatment patterns as well as costs in patients with psoriasis. This study was performed to estimate direct and indirect costs of the psoriasis population in Sweden, and to analyse changes in costs between 2006 and 2009. The study population was identified in national registers. Direct costs included health care visits with primary psoriasis diagnoses in specialist care and drugs relevant for treating psoriasis. Productivity loss, including costs of long-term sick leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…On an annualized basis, HCRU cost estimates in the 3 studies were USD 1,043 (34), USD 2,645 (35), and USD 11,356 (36). Annualized estimates of cost of productivity losses in the 3 studies were USD 1,500 (35), 3,190 (36), and approximately USD 13,500 (34). The differences may reflect patient recruitment strategy, inclusion/exclusion criteria, and differences in definition of costs.…”
Section: Discussionmentioning
confidence: 99%
“…On an annualized basis, HCRU cost estimates in the 3 studies were USD 1,043 (34), USD 2,645 (35), and USD 11,356 (36). Annualized estimates of cost of productivity losses in the 3 studies were USD 1,500 (35), 3,190 (36), and approximately USD 13,500 (34). The differences may reflect patient recruitment strategy, inclusion/exclusion criteria, and differences in definition of costs.…”
Section: Discussionmentioning
confidence: 99%
“…methotrexate) or phototherapy may be indicated in patients who do not respond to the first-line topical therapy (5). Methotrexate is the most commonly prescribed systemic agent for psoriasis in Sweden (7).…”
mentioning
confidence: 99%
“…With improved overall health, patients on biologic therapy can often improve their productivity, reduce their disability, and reduce their need for outpatient care ( Kimball et al, 2012 ; Larsen et al, 2013 ; Reich et al, 2011 ), which can have a substantial positive economic impact. For example, a recent Swedish study found that, although initiating treatment with a biologic increased the direct costs of managing psoriasis, the economic benefits of increased productivity, including reduced long-term sick leave and disability pension payments, significantly outweighed the increased direct costs ( Norlin, Steen Carlsson, Persson, & Schmitt-Egenolf, 2015 ). Such findings highlight the importance of communicating openly with patients to weigh the benefits versus costs of available treatments.…”
Section: Special Considerations For Patient Care and Helpful Tipsmentioning
confidence: 99%